Malaria prevalance and socio-acceptability of insecticide-treated bed nets for malaria prevention in Mazabuka, Zambia - Banda, Jane (2013)
Malaria is an immerse public health challenge in the world today. Although preventable, it still causes significant morbidity and mortality, accounting for over 300 to 500 million clinical episodes and annual deaths of more than 1 million people, mostly African children under 5 years old. Zambia is a high malaria transmission area recording around 4 million cases and about 6,400 deaths annually, with a casefatality rate of about 40/1,000 among Hospital admissions. This is so despite intensive scale-up of proven effective interventions to mitigate the disease. One sure way of preventing malaria is minimising human-vector contact of which insecticidetreated bed nets (ITNs) are a proven and effective tool. Bed nets are considered the most important means of achieving the 6th malaria related Millennium Development Goal (MDG6). This research sought to determine the social-acceptability of ITNs in Mazabuka, Zambia by assessing knowledge, attitudes and practices regarding malaria and ITNs. The association between the socio-demographic characteristics and KAPs were investigated. It was also in the interest of this research that the malaria prevalence in the studied area was ascertained. Pre-tested semi-structured questionnaires were administered to 177 household heads to determine their KAPs of malaria and ITNs. Three focus group discussions were conducted to triangulate the study findings including independent researcher observations. Furthermore, available data for malaria diagnosis for 2008 to 2011 were accessed at Cheeba Rural Health Centre. The mean scores (SD) of respondents’ knowledge, attitude and practice were 68.08% (26.64), 71.8% (34.59) and 36.92% (32.2) respectively. High levels of knowledge of malaria and ITNs including tertiary education as well as challenges faced were found to be predictors of consistent bed net use [OR 2.957, (95% CI =1.436-6.091, p value = 0.003)]; [OR 18.519, (95% CI = 1.704-200.000, p value = 0.012)] and [OR 18.329, (95% CI = 2.537-12.226, p value = 0.0001)] respectively. Moreover, knowledge of malaria and ITNs was shown to be significantly associated with high income [OR 8.193 (95% CI = 1.003-66.953, p value = 0.021)]. Despite the high knowledge levels, only less than half of the respondents were consistent net users and the number of nets found hanging was even lower (37.9%). This is also in agreement with the low mean practice score (36.92%). The conclusion drawn from this study therefore is that ITNs were socially accepted by the studied community. However in as much as net ownership rates were very high among households, utilisation lags behind, hence negating the expected protective benefits of ITNs. Hence, improvement in consistency of ITN utilisation is eminent if maximum benefits are to be realised.